Pengaruh Insentif Keuangan Dan Penetapan Tujuan Terhadap Kinerja Individu: Uji Eksperimen Mahasiswa Kewirausahaan - Dian Wijayanti; Uki Yonda Asepta; Rino Tam Cahyadi (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
This study aims to examine the effect of incentive schemes and participation in goal setting on performance. This study intends to test whether goal-setting theory can explain the effect of incentive schemes and individual participation in setting goals on performance achieved within a certain period. The incentive schemes tested in the study are piece-rate, quotas in relation to performance and targeting. Field experiment procedures with a 2x2 design were carried out to test the causal relationship between these variables. Experiments were carried out on 141 students with experimental tasks related to entrepreneurship courses. Data analysis and hypothesis testing were performed using Two Way Anova repeated measurement and contrast test. The results of the analysis show that the performance of the quota incentive scheme where the incentives are given based on the set targets is less than the piece-rate incentive scheme. The budget-based incentive scheme, in this case the quota incentive scheme, is not expected to provide an increase in effort. The increase in effort does not result in better performance.